1998
DOI: 10.1152/ajpgi.1998.274.2.g325
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and distal esophageal contractions have similar manometric features

Abstract: The human esophagus is composed of striated muscle proximally and of smooth muscle distally with a transition zone between the two. Striated muscle contracts much faster than smooth muscle. The change in pressure over time (dP/d t) of the contraction amplitude should therefore be higher in proximal than in distal esophagus, reflecting the presence of striated muscle proximally. There were 34 normal esophageal manometries of patients analyzed for swallow amplitude and dP/d t in the pharynx and esophagus. An add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…We performed the measurement at a site that has more than 50% of striated muscle. The manometric behavior of the striated muscle portion of the proximal esophagus shows characteristics similar to those of distal esophageal smooth muscle and different from the striated muscle of the pharynx (19). The slower contraction of the striated esophageal muscle than the striated muscle of the pharynx makes our perfusion system adequate to measure contraction.…”
Section: Discussionmentioning
confidence: 92%
“…We performed the measurement at a site that has more than 50% of striated muscle. The manometric behavior of the striated muscle portion of the proximal esophagus shows characteristics similar to those of distal esophageal smooth muscle and different from the striated muscle of the pharynx (19). The slower contraction of the striated esophageal muscle than the striated muscle of the pharynx makes our perfusion system adequate to measure contraction.…”
Section: Discussionmentioning
confidence: 92%
“…Evaluating the presence of distinct pressure zones in the esophagus Peghini et al reported a low pressure zone in 26% of patients with esophageal symptoms and 18% of healthy volunteers 16 . The difference between these and our findings (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…1). Interestingly, the proximal striated muscle of the human esophagus behaves manometrically more like the distal smooth muscle rather than like the striated muscle of the pharynx, i.e., striated muscle of the proximal esophagus contracts more slowly than expected (Peghini et al, 1998). The mechanism of this contraction delay is unclear.…”
Section: Functional Considerationsmentioning
confidence: 97%